2011
DOI: 10.1002/jcb.23155
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin interaction networks and higher order architectures of eukaryotic genomes

Abstract: Eukaryotic genome is, not only linearly but also spatially, organized into non-random architecture. Though the linear organization of genes and their epigenetic descriptors are well characterized, the relevance of their spatial organization is beginning to unfold only recently. It is increasingly being recognized that physical interactions among distant genomic elements could serve as an important mean to eukaryotic genome regulation. With the advent of proximity ligation based techniques coupled with next gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…The nonrandom topological properties of most real-world networks are strongly associated with their robustness and functional organization ( Albert et al, 2000 ; Barabási and Albert, 1999 ; Barabási and Oltvai, 2004 ), which has motivated molecular biologists to explore cellular regulation using a systems approach. Although most cellular networks, such as gene-regulatory, metabolic, protein-protein interaction, and signaling networks, are being widely studied, the extensive communications among regulatory elements in the genome have not been viewed in a complex-network context ( Singh Sandhu et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The nonrandom topological properties of most real-world networks are strongly associated with their robustness and functional organization ( Albert et al, 2000 ; Barabási and Albert, 1999 ; Barabási and Oltvai, 2004 ), which has motivated molecular biologists to explore cellular regulation using a systems approach. Although most cellular networks, such as gene-regulatory, metabolic, protein-protein interaction, and signaling networks, are being widely studied, the extensive communications among regulatory elements in the genome have not been viewed in a complex-network context ( Singh Sandhu et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Anchors in different interacting pairs are not isolated - they may overlap with or link to other counterparts in different physical regions. This leads to the concept of "chromatin interaction networks" [ 31 ], which refers to the 2D structure of genome-wide chromatin interaction (Figure 5 ). Like many cellular networks, chromatin interaction network [ 20 ] has scale-free and modular topology - most nodes participate in only one or two interactions, while a few nodes, known as "hubs", connect with a disproportionately high number of nodes.…”
Section: Applications Of Chia-pet Technologymentioning
confidence: 99%
“… Transformation from current chromatin interactions to future 3D/4D dynamics . This figure is from Sandhu et al, 2011 [ 31 ]. …”
Section: Applications Of Chia-pet Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…A commonly used tool for this is the UCSC Genome Browser [ 6 ]. However, two and three dimensional representations of chromatin interactions in the form of networks and three-dimensional models can provide a global view of the interactions and facilitate the use of established network analysis methods and measures on these datasets [ 7 ]. For example, network representation of RNA Pol2 ChIA-PET data revealed that loci harboring disease-associated SNPs are differently connected in chromatin interaction networks [ 8 ].…”
Section: Introductionmentioning
confidence: 99%